Antibiotic susceptibility testing of anaerobic bacteria by broth microdilution method using the MICRONAUT-S Anaerobes MIC plates. (June 2020) - Cordovana, Miriam; Ambretti, Simone
Abstract: Susceptibility profiles of anaerobic bacteria to antibiotics have become unpredictable, thus reliable and user-friendly methods for routine susceptibility testing are needed. In this study, we evaluated the MICRONAUT-S Anaerobes MIC test plate, a commercially available broth microdilution method, and suitable for clinical microbiology routine testing. We analyzed a collection of 300 consecutive clinically significant isolates, including 149 Gram-positive and 151 Gram-negative strains. The performance of the MICRONAUT-S Anaerobes MIC plate was compared to that of a gradient diffusion method (current laboratory standard), calculating the essential and the categorial agreement. 99.7% (299/300) of the strains included in this study successfully grew in the MICRONAUT-S Anaerobes MIC plate (73% of them after 24 h of incubation), while 1 Porphyromonas uenoni isolate didn't grow. It showed a high concordance with the gradient diffusion method. Overall essential and categorical agreements resulted >95% and >97%, respectively, and only a low rate of errors was observed. Beyond the very good analytical performance, several technical advantages in comparison with the gradient diffusion method were observed, that contribute to make the MICRONAUT-S Anaerobes panels suitable for an easy implementation into laboratory routine. Highlights: The MICRONAUT-S Anaerobes MIC test plate is a broth microdilution method for AST of anaerobes. Results of MICRONAUT-S Anaerobes plates were compared with a gradient diffusion method. All the 300 isolates grew in the MICRONAUT-S Anaerobes plates, except 1 Porphyromonas uenoni isolate. Essential agreement and categorial agreement were >95% and >97%, respectively. MICRONAUT-S Anaerobe plates proved to be a reliable and suitable method for routine practice.